Glitz, Glamour, and the Farm: Portrayal of Agriculture as the Simple Life - Amanda M. Ruth; Lisa K. Lundy; Travis D. Park (Journal of Applied Communications, 2005)
Reality television has taken America by storm with programming ranging from extreme stunts to police adventures to spoofs on segments of society. Agriculture has been a participant in the reality television boom through a series called “The Simple Life” in which two Hollywood debutantes explore the “realities” of farm life in Arkansas. This study examines the impact of this portrayal of agriculture and its effects on viewers’ impressions of the industry. Four focus groups were used to investigate the potential effects of an agriculturally based reality television show on viewers’ attitudes, opinions, and perceptions of agriculture. Results indicated those with agricultural knowledge viewed the portrayal of farm life as inaccurate and disturbing, while those without agricultural literacy found the program entertaining, if not exactly “real.” Those viewers lacking in agricultural literacy realized that the program did not accurately portray real agricultural life, but could not discern where the program failed in its accurate representation. Viewers with agricultural backgrounds found the series did not accurately reflect the amount of labor and intellectual capacity needed to produce food and fiber. The portrayal of agriculture as “hickish” and “backwoodsy” reinforced traditional stereotypes. This study suggests that the agricultural industry may be well served in further exploration of the impact of broadcast entertainment programming on the public’s agricultural literacy.